Analisis Pengaruh Contract Change Order (CCO) Terhadap Waktu Pelaksanaan Proyek Pembangunan Ruang Kelas Baru (RKB) Madrasah Tsanawiyah Negeri 6 Maluku Tengah - Romroma, Deske; Saleh, La Mohamat; Marantika, Meyke (KOLONI, 2025)
Construction projects are one of the activities that have a certain period of time. However,The purpose of this study is to obtain what factors affect the Contract Change Order (CCO) on the implementation time and find out the presentation of the influence of free variables on the implementation time of the New Classroom Construction (RKB) project of Madrasah Tsanawiyah NEGERI 6 Central Maluku. The analysis method used in this study is with the help of the SPSS program version 20. In the New Classroom Construction Project (RKB) Madrasah Tsanawiyah NEGERI 6 Central Maluku there are several factors that affect the contract change order on the implementation time. Among them are construction factors, administrative factors, resources, natural events and the presentation of the influence of independent variables on implementation time, which is 83.4% and the remaining 16.6% is influenced by other variables that were not tested in this study